2023
DOI: 10.3389/fpsyt.2023.1068431
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the problematic TikTok Use Scale among the general population

Abstract: IntroductionThis study aims to provide a scale for measuring problematic TikTok use levels by adapting items from the Instagram Addiction Scale.MethodsThe 372 participants were determined by a convenience sampling method, and data were collected through Google online forms. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed for construct validity and criterion-related validity analysis. Criterion-related validity for the Problematic TikTok Use Scale (PTTUS) was tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Research has shown that problematic TikTok use is associated with depression, social anxiety, boredom proneness, and distress intolerance [ 73 , 74 , 75 ]. A study involving Chinese high school students found that problematic TikTok use is positively linked to memory loss, depression, anxiety, and stress [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that problematic TikTok use is associated with depression, social anxiety, boredom proneness, and distress intolerance [ 73 , 74 , 75 ]. A study involving Chinese high school students found that problematic TikTok use is positively linked to memory loss, depression, anxiety, and stress [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive social media use, in general, leads to increasing procrastination levels [ 57 , 58 , 61 , 64 , 65 ] and is linked to feelings of loneliness, anxiety, and depression [ 71 , 73 , 75 ]. The widespread presence and accessibility of temptations, such as TikTok use, can be seen as an occasion to put off essential matters until later and further intensify the issue of procrastination [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations